Structural performance of shear loaded precast EPS-foam concrete half-shaped slabs - Saheed, Sanusi; Abd. Aziz, Farah N. A.; Amran, Mugahed; Vatin, Nikolai; Fediuk, Roman; Ozbakkaloglu, Togay; Gunasekaran, Murali; Mosaberpanah, Mohammad Ali (MDPI AG, 2020)
Precast concrete elements provide a feasible way to expedite on-site construction; however, typical precast components are massive, making their use particularly undesirable at construction sites that suffer from low load-bearing capacity or have swelling soils. This research aims to develop an optimal lightweight expanded polystyrene foam concrete (EPS-foam concrete) slab through a consideration of various parameters. The precast EPS-foam concrete half-shaped slabs were prepared with a density and compressive strength of 1980 kg/m3 and 35 MPa, respectively. Quarry dust (QD) and EPS beads were utilized as substitutions for fine and coarse aggregates with replacement-levels that varied from 5% to 22.5% and 15% to 30%, respectively. The use of EPS beads revealed sufficient early age strength; at the same time, the utilization of quarry dust in EPS-foam concrete led to a more than 30% increase in compressive strength compared to the EPS-based mixtures. Two hundred and fifty-six trial mixes were produced to examine the physical and mechanical characteristics of EPS-foam concrete. Three batches of a total of four EPS-foam concrete half-shaped slabs with spans of 3.5 and 4.5 m and thicknesses of 200 and 250 mm were prepared. Findings showed that the ultimate shear forces for the full-scale EPS-foam concrete half-shaped slabs were approximately 6–12% lower than those of the identical concrete samples with a 2410 kg/m3 average density, and 26–32% higher than the theoretical predictions. Also, it was observed that the self-weight of EPS-foam concrete was reduced by up to 20% compared to the control mixtures. Findings revealed that the prepared precast EPS-foam concrete half-shaped slabs could possibly be applied as flooring elements in today’s modern infrastructure.